The outbreak of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2): A review of the current global status - Mbarka Bchetnia; Catherine Girard; Caroline Duchaine; Catherine Laprise (Elsevier, 2020)
There is currently an ongoing worldwide pandemic of a novel virus belonging to the family of Coronaviruses (CoVs) which are large, enveloped, plus-stranded RNA viruses. Coronaviruses belong to the order of Nidovirales, family of Coronavirinae and are divided into four genera: alphacoronavirus, betacoronavirus, gammacoronavirus and deltacoronavirus. CoVs cause diseases in a wide variety of birds and mammals and have been found in humans since 1960. To date, seven human CoVs were identified including the alpha-CoVs HCoVs-NL63 and HCoVs-229E and the beta-CoVs HCoVs-OC43, HCoVs-HKU1, the severe acute respiratory syndrome-CoV (SARS-CoV), the Middle East respiratory syndrome-CoV (MERS-CoV) and the novel virus that first appeared in December 2019 in Wuhan, China, and rapidly spread to 213 countries as of the writing this paper. It was ofﬁcially named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by the international committee on taxonomy of viruses (ICTV) and the disease's name is COVID-19 for coronavirus disease 2019. SARS-CoV-2 is very contagious and is capable of spreading from human to human. Infection routes include droplet and contact, and aerosol transmission is currently under investigation. It is associated with a respiratory illness that may cause severe pneumonia and acute respiratory distress syndrome (ARDS). SARS-CoV-2 became an emergency of international concern. As of July 12, 2020, the virus has been responsible for 12,698,995 confirmed cases and 564,924 deaths worldwide and the number is still increasing. Up until now, no specific treatment has yet been proven effective against SARS-CoV-2. Since the beginning of this outbreak, several interesting papers on SARS-CoV-2 and COVID-19 have been published to report on the phylogenetic evolution, epidemiology, pathogenesis, transmission as well as clinical characteristics of COVID-19 and possible treatments agents.This paper is a systematic review of the available literature on SARS-CoV-2. It was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and aims to help readers access the latest knowledge surrounding this new infectious disease and to provide a reference for future studies.